On new military technologies and concepts explored from the Syrian conflict experience - Nikolić, Nebojša V. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The purpose of this paper is to presents some tendencies stemming from the experiences from the ongoing Syrian conflict towards the development of new military concepts and technologies. The manner, scope and dynamics of exploitation of the combat experience from the Syrian conflict is a good example how great powers improve the capabilities of their defense systems. Methods: An extensive content analysis of selected reference sources has been applied. The system approach was used for a structural and balanced presentation of the available information. The comparative analysis has confirmed some similarities in the behavior of the great powers in terms of deploying and testing complex combat systems of strategic importance in local wars. Inductive thinking has contributed to the synthesis of appropriate conclusions. Results: Among the presence of several great and regional powers heavily involved in this conflict, Russia’s is considered to be the most dominant and as such is the main subject of investigation in this paper. Field testing of new military equipment is known to be important but of extreme importance is its testing under real combat conditions. In parallel with intensive testing of a wide range of military technologies, there are indicators of developing new concepts, doctrines, and organizational upgrades on the basis of the Syrian combat experiences. Conclusion: From the standpoint of military technology and concept development, the Russian endeavor in Syria has become an example of a comprehensive and systematic aproach to learning, training, innovations, and implementations of the most relevant factors in the development of a modern military organization as a response to challenges of contemporary armed conflicts.